High school students on reasons for absenteeism in physical education classes - Jastrzębska, Joanna (Journal of Education, Health and Sport, 2022)
The aim of the study was an attempt to diagnose the phenomenon of absenteeism in PE lessons of high school youth. The survey included 51 randomly selected students aged 14-18 from a selected high school in Lodz. The research was carried out on the basis of the diagnostic survey method and the survey technique, while the research tool was a questionnaire constructed for the needs of the pilot studies, containing closed, semi-open and open questions The results of the research were subjected to statistical analysis, determining the significance of differences using the chi-square test. The research results indicate that girls (36,7%) less often and less willingly participate in PE lessons than boys (66,7%). The main reasons for absenteeism from physical education lessons are the teacher’s approach and the way of conducting classes (7,9%); lack of awareness and knowledge of the benefits of physical activity (31,4%); lack of encouragement to take up physical activity on the part of relatives and the teacher (8%), and shame caused by the appearance of the body (13,5%).